Fixations, regressions, and results: eye-tracking metrics as real-time signals of cognitive engagement in flipped-class quizzes - Wang, Yuanyuan; Xie, Nina; Liu, Yujun (Frontiers in Education, 2025)
IntroductionEducators need real time evidence of how students process pre class quiz items in flipped courses, not just whether answers are right or wrong. We examined whether two classroom feasible eye tracking metrics—fixation intensity (total dwell time) and regression rate (proportion of backward saccades)—provide interpretable, item level signals of cognitive engagement once surface text features are taken into account.MethodsThirty four undergraduates completed 320 analysable attempts on 55 multiple choice items coded by Bloom’s taxonomy while a 60 Hz tracker recorded gaze. Crossed mixed effects models included a covariate for each item’s total word count. A logistic mixed model tested whether fixation intensity and regression rate predicted correctness beyond Bloom level, gender, and length. After each block, students reported perceived mental effort to compare subjective and gaze based indicators.ResultsAfter controlling for total word count, Bloom category did not uniquely predict fixation intensity or regression rate, suggesting that previously observed demand patterns largely reflected text length. In the accuracy model, fixation intensity showed a small, positive association with being correct, whereas regression rate showed a small, negative association.DiscussionIn authentic flipped class quizzes, fixation intensity and regression rate can serve as complementary, real time indicators of engagement, but only when item length and layout are standardised or statistically modelled. Claims about differences across Bloom levels should be made cautiously. We outline design guidance for future item banks—length matched stems, fixed numbers of options, and pre registered word count covariates—to enable firmer inferences and practical classroom diagnostics.